Evaluation of the Ecotoxicological Effects of Microcystis aeruginosa and Cylindrospermopsis raciborskii on Ceriodaphnia dubia Before and After Treatment with Ultrasound - Lira, Vivian Silva [UNESP]; Moreira, Ingritt Caroline; Tonello, Paulo Sérgio [UNESP]; Henriques Vieira, Armando A.; Fracácio, Renata [UNESP] (Springer Nature, 2017)
Bodies of water contaminated by cyanobacteria and their neuro- and hepatotoxins have caused environmental and public health issues all over the world. Therefore, determining safe concentrations in water for multiple uses to protect aquatic biota and identify forms of remediation are of broad interest. In this study, we isolated strains of the cyanobacteria Microcystis aeruginosa and Cylindrospermopsis raciborskii, which produce microcystin (MC) and saxitoxin (STX), respectively. Ecotoxicological tests using suspensions of lysed lyophilizated cells with concentrations of toxins equivalent to those permitted by legislation for potability (1 μg L−1for MC and 3 μg L−1for STX) did not result in significant mortality of the model organism, Ceriodaphnia dubia, where as concentrations five times greater resulted in decreased survival for both toxins. However, reproduction was significantly reduced even in the lower concentrations, indicating that the currently permitted standards are not safe for environmental protection. When cyanotoxins were treated with ultrasound, mortalities were no longer significant, independent of concentrations. Although reproduction was still lower in relation to the control, it was significantly higher when compared to the results obtained before ultrasound. Ultrasound has been previously applied to cyanobacteria cell lysis, but this is the first study to investigate the ecotoxicological effects of ultrasound on cyanotoxins. Using new test organisms and different times and potency of sonication will permit the development of more efficient techniques for the remediation of these toxins and the development of more adequate parameters for the protection of aquatic life.
Keywords: Ceriodaphnia dubia; Cylindrospermopsis raciborskii; Microcystin; Microcystis aeruginosa; Saxitoxin; Ultrasound